2021
DOI: 10.1002/app.50621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyphosphoric acid (PPA), styrene‐butadiene‐styrene (SBS), or rock asphalt on the performance of desulfurized rubber modified asphalt

Abstract: To improve the performance of desulfurized rubber modified asphalt (DRMA), especially its high-temperature performance, three modifiers (including polyphosphoric acid [PPA], styrene-butadiene-styrene [SBS], and rock asphalt) were selected to modify DRMA respectively. The conventional performance, rheological properties, chemical composition, and thermal decomposition were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…At a mass loss of 50%, the decomposition temperatures of SBSMA, RP/SBSMA, and TA‐TPC‐Rubber/SBSMA were 460, 456, and 458°C, respectively. These temperature values were quite similar; however, after the first decomposition stage, the remaining mass of TA‐TPC‐Rubber/SBSMA with the highest decomposition temperature is slightly higher than that of RP/SBSMA and greater than SBSMA, indicating that TA‐TPC‐Rubber can effectively improve the high‐temperature stability of SBSMA 40 . This may be due to the strong RP chain and ester bond formed by cross‐linking TA and TPC, which requires more heat for cleavage and hence TA‐TPC‐Rubber/SBSMA realized higher thermal stability 41,42 …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…At a mass loss of 50%, the decomposition temperatures of SBSMA, RP/SBSMA, and TA‐TPC‐Rubber/SBSMA were 460, 456, and 458°C, respectively. These temperature values were quite similar; however, after the first decomposition stage, the remaining mass of TA‐TPC‐Rubber/SBSMA with the highest decomposition temperature is slightly higher than that of RP/SBSMA and greater than SBSMA, indicating that TA‐TPC‐Rubber can effectively improve the high‐temperature stability of SBSMA 40 . This may be due to the strong RP chain and ester bond formed by cross‐linking TA and TPC, which requires more heat for cleavage and hence TA‐TPC‐Rubber/SBSMA realized higher thermal stability 41,42 …”
Section: Resultsmentioning
confidence: 84%
“…The Superpave specification requires a viscosity of no more than 3 Pa·s at 135°C to facilitate storage and pumping during construction. However, it is difficult for the asphalt modified by RP to meet this requirement, 40 and higher temperature is needed to attain a viscosity of 3 Pa·s. Therefore, during the storage, mixing, and construction application, RP/SBSMA needs to be heated to a higher temperature 44 …”
Section: Resultsmentioning
confidence: 99%
“…NR has two main types: natural rubber latex (NRL) and a new type of NR known as cup lump natural rubber (CLNR) (Figure 1), which is produced when latex is allowed to coagulate under bacterial attack [12,13]. NRL polymer can be used as a modifier to enhance bitumen's physical qualities, such as increasing the softening point, reducing penetration while enhancing the penetration index, and improving the properties of shortand long-term ageing [3,14,15]. NRL also addresses the common problems of bitumen, such as fatigue, permanent deformation, fracture strength and thermal cracking resistance, helping improve the durability of bitumen pavement [5,16].…”
Section: Natural Rubber As a Bitumen Modifiermentioning
confidence: 99%
“…Latex-modified bitumen does not experience phase separation during hot-temperature storage due to improved viscoelastic capabilities. Morphological analysis revealed that the material has a homogeneous dispersed network [14,18]. such as fatigue, permanent deformation, fracture strength and thermal cracking resistance, helping improve the durability of bitumen pavement [5,16].…”
Section: Natural Rubber As a Bitumen Modifiermentioning
confidence: 99%
“…Natural rock asphalt refers to the asphalt that exists in rock crevices, which is often used as an additive and modifier for asphalt materials [ 1 , 2 , 3 , 4 , 5 ]. Buton Rock Asphalt (BRA) is a kind of rock asphalt that originates from Buton Island, Sulawesi province, Indonesia [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%